1,8-Dimercuri-6-Phenyl-1H-Carbazole as a Monofacial Dinuclear Organometallic Nucleobase - Dattatraya Uttam Ukale; Petri Tähtinen; Tuomas Lönnberg (WILEY-V C H VERLAG GMBH, 2022)
A C-nucleoside with 6-phenyl-1H-carbazole as the base moiety has been synthesized and incorporated in the middle of an oligonucleotide. Mercuration of this modified residue at positions 1 and 8 gave the first example of an oligonucleotide featuring a monofacial dinuclear organometallic nucleobase. The dimercurated oligonucleotide formed stable duplexes with unmodified oligonucleotides placing either cytosine, guanine, or thymine opposite to the organometallic nucleobase. A highly stabilizing (Delta T-m=7.3 degrees C) Hg-II-mediated base pair was formed with thymine. According to DFT calculations performed at the PDE0DH level of theory, this base pair is most likely dinuclear, with the two Hg-II ions coordinated to O2 and O4 of the thymine base.